Parent-adolescent conflict a social cognitive perspective - Bennagen, Trisha C. 1974- (2000)
This is an exploratory study which examines cognitions of parents and adolescents at the interpersonal and intergroup levels. It hypothesizes that the greater the divergence between cognitions of adolescents and cognitions of parents, the greater is the conflict that occurs between them. It also proposes that parent-adolescent conflict accurs both at the interpersonal and intergroup levels. At the interpersonal level, information processing by the parent and the parent and the adolescent is individuated. The parent sees himself/herself as "the parent of my child" and the child as "my child". The adolescent perceives himself/herself as "the child of my parents" and his/her parent as "my parent". However, parents and adolescents are not only part of a dyadic relationship, they are also members of larger social categories. Every parent is part of the social category of parents and every adolescent is a member of the social category adolescents. At the intergroup level, parents and adolescents see themselves and the other not only from the standpoint of an individual parent or child but also from the standpoint of a particular social category membership. Questionnaires were administered to two groups of parent-adolescent pairs, the high-confilct and low-conflict groups. Each group has 25 female adolescent-parent pairs and 25 male adolescent-parent pairs. Answers of each adolescent on each item were compared to the answers of their parent on the parallel item. Results show that adolescents and parents think differently about the same topic, issues, and situations that are relevant to parent-adolescent conflict. Adolescentsand parents from the low-conflict group have more positive cognitions than adolescents and parents from the high-conflict group. Results confirm the hypothesis of the study. Parent-adolescent conflict at the interpersonal level tends to occur when: 1) the parents and the adolescent have a bias in favor of the self; 2) the parents and the adolescent have negative perceptions of the self and the other; 3) the parent sees himself/herself more positively than the adolescent perceives his/her own parent: and 4) there is a great divergence between the adolescent's self-perception and the parent's perception of his/her own adolescent child and between the adolescent's perception of his/her own parent and the parent's self-perception. Parent-adolescent conflict at the intergroup level tends to occur when: 1) the parent and the adolescent have negative perceptions of parents and adolescents in general; 2) the adolescent perceives the social category of parents (their out-group schema) more positively than he/she perceives his/her own parent; 3) where there is a great divergence between adolescents and parents' perception of parents as a social category (group schema of parents). The study suggests that cognitions are important in studying parent-adolescent conflict. Conflict may not be directly observed through behavior but may be felt both by the parent adn the adolescent. This conflict may be seen by examining their cognitions.